Signal Processing and Information Technology First International Joint Conference, SPIT 2011 and IPC 2011, Amsterdam, The Netherlands, December 1-2, 2011, Revised Selected Papers - Das, Vinu V.; Ariwa, Ezendu; Rahayu, Syarifah Bahiyah; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the First International Joint Conference on Advances in Signal Processing and Information Technology (SPIT 2011) and Recent Trends in Information Processing and Computing (IPC 2011) held in Amsterdam, The Netherlands, in December 2011. The 50 revised full papers presented were carefully selected from 298 submissions. Conference papers promote research and development activities in computer science, information technology, computational engineering, image and signal processing, and communication.
Keywords: Computer science; Computer communication systems; Software engineering; Algorithms; Information storage and retrieval; Artificial intelligence; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Information Storage and Retrieval; Software Engineering; Electronic books